2020
DOI: 10.1111/gcb.15230
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring coral: Anthropogenic nutrients shift diverse coral–symbiont nutrient and carbon interactions toward symbiotic algal dominance

Abstract: Improving coral reef conservation requires heightened understanding of the mechanisms by which coral cope with changing environmental conditions to maintain optimal health. We used a long‐term (10 month) in situ experiment with two phylogenetically diverse scleractinians (Acropora palmata and Porites porites) to test how coral–symbiotic algal interactions changed under real‐world conditions that were a priori expected to be beneficial (fish‐mediated nutrients) and to be harmful, but non‐lethal, for coral (fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…In the Florida Keys, this pattern is compounded by a cross‐shelf gradient in water quality, characterized by decreasing turbidity and nutrient concentrations moving away from shore (Lapointe et al, 2019; Lirman & Fong, 2007). Variation in water quality parameters, such as overall nutrient load, dissolved nutrient stoichiometry and the concentration of suspended particulate matter, can dramatically alter coral physiology (Allgeier et al, 2020; Anthony & Fabricius, 2000; Koop et al, 2001) and have been shown to diminish coral resistance to bleaching and disease (DeCarlo et al, 2020; Vega Thurber et al, 2014; Wiedenmann et al, 2013). It is likely that the combined pressure of these cross‐shelf gradients in temperature and water quality conditions is responsible for the observed genetic specialization to each reef zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Florida Keys, this pattern is compounded by a cross‐shelf gradient in water quality, characterized by decreasing turbidity and nutrient concentrations moving away from shore (Lapointe et al, 2019; Lirman & Fong, 2007). Variation in water quality parameters, such as overall nutrient load, dissolved nutrient stoichiometry and the concentration of suspended particulate matter, can dramatically alter coral physiology (Allgeier et al, 2020; Anthony & Fabricius, 2000; Koop et al, 2001) and have been shown to diminish coral resistance to bleaching and disease (DeCarlo et al, 2020; Vega Thurber et al, 2014; Wiedenmann et al, 2013). It is likely that the combined pressure of these cross‐shelf gradients in temperature and water quality conditions is responsible for the observed genetic specialization to each reef zone.…”
Section: Discussionmentioning
confidence: 99%
“…In the Florida Keys, this pattern is compounded by a cross-shelf gradient in water quality, characterized by decreasing turbidity and nutrient concentrations moving away from shore (Lapointe et al, 2019;Lirman & Fong, 2007). Variation in water quality parameters, such as overall nutrient load, dissolved nutrient stoichiometry and the concentration of suspended particulate matter, can dramatically alter coral physiology (Allgeier et al, 2020;Anthony & Fabricius, 2000;Koop et al, 2001) and have been shown…”
Section: Environmental Specialization Across Reef Zonesmentioning
confidence: 99%
“…In the Florida Keys, this pattern is compounded by a cross-shelf gradient in water quality, characterized by decreasing turbidity and nutrient concentrations moving away from shore (Lapointe et al, 2019; Lirman & Fong, 2007). Variation in water quality parameters, such as overall nutrient load, dissolved nutrient stoichiometry, and the concentration of suspended particulate can dramatically alter coral physiology (Allgeier et al, 2020; Anthony & Fabricius, 2000; Koop et al, 2001) and has been shown to diminish coral resistance to bleaching and disease (DeCarlo et al, 2020; Vega Thurber et al, 2014; Wiedenmann et al, 2013). It is likely that the combined pressure of these cross-shelf gradients in temperature and water quality conditions is responsible for the observed genetic specialization to each reef zone.…”
Section: Discussionmentioning
confidence: 99%
“…This was further confirmed by the results of δ 13 C values showing no difference among different pH treatments (Figure 2C). The natural C isotope abundance has been used to understand the balance of autotrophy and heterotrophy in hermatypic corals (Wall et al, 2020), with the δ 13 C values positively relating to the photosynthate or autotrophic input (Tremblay et al, 2015;Allgeier et al, 2020). Therefore, the similar δ 13 C values among different pH treatments suggest stable PFC assimilation.…”
Section: Discussionmentioning
confidence: 99%